Analisis Yuridis Terhadap Sengketa Hak Milik Atas Tanah Di Kabupaten Takalar - Kifliansyah, Baso; Marilang, Marilang; Talli, Halim (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2022)
The main problem of this research is the Juridical Analysis of Land Ownership Disputes in Takalar Regency. This research is descriptive research using qualitative data, data obtained through field studies (Field Research). so that the data collection method is sourced from informant data from both the Plaintiff and the Defendant, the Takalar District Court, and from the government in this case the Lakatong Village. Data was collected through the methods of observation, interviews and documentation. Furthermore, the data obtained will be analyzed through a Juridical Sociology approach. The conclusions from the results of this study are: 1) the problem is that the land located in Kaporengeng, Lakatong Village, Manggarabombang District, Takalar Regency (the object of the current dispute) is the land owned by Samsu B Peleng based on the detailed letter of Pesil No. 8a D1 Kohir 30 covering an area of ​​± 10 acres (1000 m²) with boundaries according to the results of local inspections, 2) based on legal considerations for the petitum which basically states that ACCUSED I controls the Disputed Land I, Rinkik land with an area of ​​:±4Are(± 400M2 Lompo Kaponrengang Persil No. 8a D1 Kohir Number 30 is an unlawful act (onrechtmatige daad) and ACCUSED II is in control of Disputed Land II, detailed land with an area of ​​:±2Are (±200M2 Lompo Kaponrengang Persil No. 8a D1 Kohir Number 30 is an act Against the law (onrechtmatige daad), 3) ​​Dictum / Amar Decision is to partially grant the claim of the plaintiffs. Keyword: Land Dispute, Property Rights